Computer simulation of discharge channel propagation in solid dielectric; ICSD '01, 25-29 Jun 2001, Eindhoven, the Netherlands - Noskov M. D. Mikhail Dmitrievich; Lopatin V. V. Vladimir Vasilyevich; Cheglokov A. A.; Shapovalov A. V. Aleksandr Vasilyevich (2001, 2001)
Title screen